A Framework For The Adoption And Effective Use Of Icts For Visually Impaired Learners In Higher Education - Tom, Sheethal, Liz (Central University of Technology, Free State, 2020)
Education is a vital asset that makes a valuable contribution in society. That is because it helps shape people into responsible citizens. Citizens who attain higher education play an important role in the economic stability and social prosperity of a nation. It is therefore imperative that all individuals in a country are assured of equal educational opportunities. The South African Constitution has embraced an inclusive education policy to ensure that no student is left behind in the education system. Inclusive education is an educational system that is designed in such a way that addresses the needs of all the students regardless of their disabilities. Special schools in South Africa cater for the educational needs of learners with disabilities. However, various researchers have observed that learners who are visually impaired are often excluded from participating in higher education institutions, especially in Engineering courses. Consequently, it is essential to identify the challenges that visually impaired learners in South Africa face when contemplating entry into higher education and more specifically, Engineering courses. Unlike other courses such as Management and Education, Engineering courses are more practical-based. That is because Engineering courses are visual in nature, especially subjects such as Computer Science, IT and Electrical Engineering which might prove challenging to visually impaired learners. Therefore, such learners require the assistance of specialised Information and Communications Technology (ICT) tools and resources for studying Engineering courses. ICT has revolutionised the education sector by facilitating the teaching and learning process of visually impaired learners. This study aims to develop a framework for the provision of visually impaired learners in Engineering education in SA using ICTs. This study also examines the ICT tools that could be adopted to better facilitate the entry of visually impaired learners into Engineering courses. A design science research paradigm is used in this study. The study started with an intensive literature review, followed by a case study which was divided into two parts: Part A and Part B. Part A of the case study was done at school level and utilised focus groups and questionnaires from educators at special schools. Part B of the case study was conducted at university level and utilised questionnaires to collect data from disability units at universities; HODs and senior lecturers from Engineering faculties at universities. The data collected from all the data sources were triangulated to develop the proposed framework for the study. The proposed framework for the provision of visually impaired learners in Engineering education in SA using ICTs comprised six components: government and management support; finance; infrastructure; mobility; teaching and learning; and student support services. The framework was evaluated by specific field experts so as to establish its validity and refine its suitability for higher education in SA. The proposed framework was refined based on the feedback from the experts. Experts consisted of a group of researchers who had done research in Engineering education, HODs of Engineering faculties, managers of disability centres and a visually impaired person working in an Engineering/IT field. Consequently, a modified framework is presented in this thesis. The scientific contribution of this study is the provision of a framework that may be used to provide better access to Engineering courses for VILs in higher education in South Africa using ICT’s. This research has identified six principal factors and twenty-one sub-factors that would assist the provision of VILs in Engineering education. Establishing such a framework could provide improved academic access for VILs in SA, thereby increasing their prospects of employment and empowerment. Accommodating VILs in the labour sector of SA will improve their quality of life, thereby contributing to the country’s economic prosperity.
Thesis